1982
DOI: 10.1002/ajh.2830130205
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hemoglobin in women with normal and with hydatidiform molar pregnancy

Abstract: The quantity and the rate of synthesis of fetal hemoglobin (HbF); the level of HbF-containing erythrocytes (F cells); and the levels of progesterone, human chorionic gonadotropin (HCG), and human chorionic somatomammotropin (HCS) in serial blood samples from women at different stages of pregnancy were determined. An increase was observed in the synthesis and the quantity of maternal HbF, reaching a peak at about 9-12 weeks gestation. A major peak in F-cell level was also detected at about 9-12 weeks, with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…In this study, %Hb F level was significantly elevated during 1 st trimester compared with those during 2 nd and 3 rd trimesters, consistent with the results of previous studies in which the proportion of red cells containing Hb F peaked during pregnancy between 2 and 7 months of gestation [8,9]. Although elevation of %Hb F level occurs as a result of either FMH or an increase in the number of adult F cells [6], the increase in red cells containing Hb F during the earlier stages of pregnancy has been suggested to be due to an increased number of adult F cells [8,9].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, %Hb F level was significantly elevated during 1 st trimester compared with those during 2 nd and 3 rd trimesters, consistent with the results of previous studies in which the proportion of red cells containing Hb F peaked during pregnancy between 2 and 7 months of gestation [8,9]. Although elevation of %Hb F level occurs as a result of either FMH or an increase in the number of adult F cells [6], the increase in red cells containing Hb F during the earlier stages of pregnancy has been suggested to be due to an increased number of adult F cells [8,9].…”
Section: Discussionsupporting
confidence: 92%
“…Although elevation of %Hb F level occurs as a result of either FMH or an increase in the number of adult F cells [6], the increase in red cells containing Hb F during the earlier stages of pregnancy has been suggested to be due to an increased number of adult F cells [8,9]. However, fetal red cells entering the maternal circulation may contribute to some extent to the elevation of %Hb F level in the 1 st trimester.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal erythrocytes and trophoblasts derive from different cell types, and these cells have dissimilar functions. Therefore, our interpretation of the data is that transplacental trafficking of fetal hematopoietic cells, along with the physiologic increase in maternal ␥-globin synthesis during pregnancy, is likely to be responsible for the observed higher concentrations of ␥-globin mRNA in the plasma of pregnant women (7,11 ).…”
Section: Clinical Chemistrymentioning
confidence: 99%
“…Wataganara et al (4 ) reported detection of ␥-globin mRNA in maternal plasma. However, expression of ␥-globin is not a fetus-specific phenomenon and is shared by maternal erythroid cells (5 ), and ␥-globin mRNA is readily detectable in nonpregnant individuals (4 ). In this study, we assessed whether rhesus D (RHD gene) mRNA derived from fetal erythroid cells is detectable in the plasma of rhesus D-negative pregnant women.…”
Section: Fetal Rhesus D Mrna Is Not Detectable In Maternal Plasmamentioning
confidence: 99%